Combining abiraterone and radiotherapy in metastatic castration-resistant prostate cancer: a review of current evidence. Issue 4 (August 2019) - Livi, Lorenzo; Detti, Beatrice; Francolini, Giulio; Terziani, Francesca; Triggiani, Luca; D'Angelillo, Rolando M.; Ingrosso, Gianluca
Prostate cancer is the second most frequent cancer worldwide, with a very high rate of progression despite treatment. The most aggressive form of the disease is known as castration-resistant prostate cancer, which carries a poor prognosis. We reviewed available literature regarding the combination of abiraterone acetate antihormonal drug and ablative radiation therapy for the treatment of metastatic castration-resistant prostate cancer. This dual treatment may enhance the effects of second-line hormonal therapy, as radiotherapy renders cancer cells more prone to immune-mediated cytotoxicity. Moreover, radiotherapy exerts its effect both on directly irradiated cells and on other distant tissues, with an abscopal effect, already demonstrated in other solid tumors. This combination treatment is safe and effective, with few adverse events. Moreover, it is of paramount importance in patients with oligoprogression of the primary disease, when current guidelines recommend continuing abiraterone treatment. Ablative radiation therapy is a noninvasive, nontoxic treatment with very high efficacy on local tumor growth control. In the available literature, the combination of radiation therapy and abiraterone acetate has prolonged both overall survival and progression-free survival, with a positive impact also on locoregional recurrence and distant metastases.